"Les Ruses de la Poétique". Michelet and the Issue of Foundational Narratives in Jacques Rancière (A Lecture on "Les Noms de l’Histoire") - Pinilla Cañadas, Scheherezade (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
This paper is conceived as an excercise in what Jacques Rancière calls poétique du savoir (poetics of knowledge). The first section could be defined as Rancierian in the sense of seeking to become a search for the literary procedures –what is called here les ruses de la poétique– by which a particular form of knowledge (Jacques Rancière’s lectures on Jules Michelet’s art of making the people speak) establishes itself as a scientific discourse. The second section could be defined as anti-Rancierian in the sense of elaborating on the possibility that the story operates as the bridge to go deeper, to achieve the History in order to uncover something more than just a partage de police in Michelet’s silent people.
Keywords: Rancière; Michelet; Poétique du Savoir; People.